Exploring The Role of Technology in Facilitating Academic Fraud in Universities: Literature Review: Akuntansi - Natawiria, Muhammad Dava; Widyaningsih, Aristanti; Arief, Meta (VISA: Journal of Vision and Ideas, 2024)
This research aims to determine the role of technology in facilitating academic cheating at universities. This research uses a systematic literature review (SLR) method, which identifies, evaluates, and interprets results from various sources related to previous research topics from 2018 - 2023. The research method uses the publish or publish platform as the main source for searching for scientific articles. An article search was carried out with the title the role of technology in Facilitating Academic Fraud (fraud) and academic cheating at Universities. This research shows that academic fraud is an opportunity to use illicit methods to steal other people's work for personal gain. Academic cheating is a problem in the current era of online learning. Cheating is a type of academic cheating that often occurs when a student is studying.